The Utilization of Tofu Pulp Waste to Create New Business Opportunities in Cinangka Sawangan Depok - Wahyudi, Wahyudi; Diana, Ayu; Ginting, Febrian Dolinta; Situmeang, Johana Neli; Nurjanah, Lilis; Pitaloka, Mayang Puspa; Anggraini, Ria; Rahmawati, Yulita Priswarizki; A’La, Zakiatul (Community: Jurnal Pengabdian Kepada Masyarakat, 2025)
The focus of this activity is to increase the use of tofu pulp waste into products of economic value through innovation in making tofu pulp crackers in Cinangka Village, Sawangan, Depok City. The implementation method uses a participatory approach with stages of initial survey, socialization and education, practical training, and monitoring and evaluation. The target of the activity is PKK women who have the potential to develop local food-based businesses. The results of the activity showed an increase in the knowledge and skills of participants in processing waste into ready-to-sell products, with a success rate of 90%. The tofu dregs cracker products produced have good taste and are suitable for development as a home business. This activity has a positive impact on community economic empowerment and supports the concept of circular economy through environmentally friendly waste management. Thus, this program can be a model of sustainable service that integrates environmental, economic, and social aspects in one community empowerment activity.